QUINTESSENCE AND PHANTOM ENERGY INHOMOGENEITIES AT LATE STAGES OF UNIVERSE EVOLUTION - Burgazli, A.; Eingorn, M.; Zhuk, A. (Одеські астрономічні публікації, 2012)
As it directly follows from the scalar perturbations, applied to the late stages of evolution of the Universe, filled with dark energy, nonrelativistic matter and, possibly, quintessence or phantom energy, the last two components can not be homogeneous. We demonstrate that ω=-1/3 is only admissible negative parameter in the non-vacuum equation of state, determine the corresponding gravitational potentials and discuss their main properties.